Juridical Analysis of the Decision of PTUN Number: 93/G/2019/PTUN-MDN concerning Disrespectful Dismissal and the Application of the Non-Rectoractive Principle in the Perspective of Fiqh Siyasah - Akhyar Khairandi Munthe; Putri Eka Ramadhani (Journal Equity of Law and Governance, 2024)
This research analyzes the Decision of the State Administrative Court (PTUN) Number 93/G/2019/PTUN-MDN, which relates to cases of dishonorable dismissal of employees and the application of the non-retroactive principle. This research uses a normative juridical approach to evaluate how the PTUN applies the principle of non-retroactivity in the context of administrative law and the principles of administrative justice. This research aims to examine the suitability of PTUN decisions with the principles of administrative law and non-retroactive principles and to evaluate these decisions from the perspective of Fiqh Siyasah, namely public law in Islam. This research aims to examine the suitability of PTUN decisions with the principles of administrative law and non-retroactive principles and to evaluate the decision from the perspective of Fiqh Siyasah, namely public law in Islam. A normative juridical approach is used to analyze the relevant legal norms and the principles of Fiqh Siyasah applied in the decision. This research assesses the application of the non-retroactive principle in the context of employee dismissal and how PTUN decisions are in accordance with the principles of justice and legal certainty. PTUN Decision Number 93/G/2019/PTUN-MDN shows the correct application of the non-retroactive principle, namely that administrative actions such as dishonorable dismissal must be based on the regulations in effect at the time the action was carried out, not the regulations in effect afterwards. Implementation of this principle protects employee rights and ensures certainty